Memahami Perilaku Kepatuhan Pajak Dengan Persepsi Teori Atribusi - Arina Nurul Hidayah; Indriyana Puspitosari (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
This study aims to determine the effect of Perceived Fairness of the Taxation System, Coercive Measures, Perceptions of Efficiency and Transparency of Government Spending, Perceptions of Trust in Government and Tax Authorities, Taxation Knowledge, Personal Financial Constraints, Reference Groups, Personal Ethics and Moral Standards, and Simplicity of Taxation Regulations as X on Tax Compliance Behavior as Y. The data used in this study are primary data. The population in this study were individual taxpayers (WPOP) at KPP Pratama Surakarta. The number of samples in this study were 100 respondents with accidental sampling technique. This study used a questionnaire as data collection. Data analysis using multiple regression analysis. The results of the analysis show that the Perception of the Fairness of the Taxation System, Coercive Action, Perception of the Efficiency and Transparency of Government Expenditure, Perception of Trust in Government and Tax Authorities, Taxation Knowledge, Personal Ethics and Moral Standards, and Simplicity of Tax Regulations have a positive and significant effect on Tax Compliance Behavior. Meanwhile, Personal Financial Constraints and Reference Groups have no effect on Tax Compliance Behavior.